TAXATION OF E-COMMERCE TRANSACTIONS: ANALYZING TURNOVER TAX IN ONLINE SALES - Khasanova Nodira Marifjonovna (Scholar Express Journals, 2025)
The rapid expansion of e-commerce has significantly transformed the global retail landscape, presenting new challenges for taxation authorities. Turnover tax in online sales has become a critical subject in tax policy, necessitating effective strategies for fair revenue collection while ensuring business compliance. This article examines the implications of turnover tax in e-commerce, exploring its economic effects, legal frameworks, and enforcement mechanisms. By analyzing case studies and international practices, we aim to provide insights into optimizing taxation policies to accommodate the digital economy.
Keywords: E-commerce taxation; turnover tax; digital economy